An Ontology-Based Representation of Vaulted System for HBIM - Mattia Previtali; Raffaella Brumana; Chiara Stanga; Fabrizio Banfi (Applied Sciences, 2020)
In recent years, many efforts have been invested in the cultural heritage digitization: surveying, modelling, diagnostic analysis and historic data collection. Nowadays, this effort is finalized in many cases towards historical building information modelling (HBIM). However, the architecture, engineering, construction and facility management (AEC-FM) domain is very fragmented and many experts operating with different data types and models are involved in HBIM projects. This prevents effective communication and sharing of the results not only among different professionals but also among different projects. Semantic web tools may significantly contribute in facilitating sharing, connection and integration of data provided in different domains and projects. The paper describes this aspect specifically focusing on managing the information and models acquired on the case of vaulted systems. Information is collected within a semantic based hub platform to perform cross correlation. Such functionality allows the reconstructing of the rich history of the construction techniques and skilled workers across Europe. To this purpose an ontology-based vaults database has been undertaken and an example of its implementation is presented. The developed ontology-based vaults database is a database that makes uses of a set of ontologies to effectively combine data and information from multiple heterogeneous sources. The defined ontologies provide a high-level schema of a data source and provides a vocabulary for user queries.